Factores sociales y culturales asociados al embarazo en adolescentes que acuden al Hospital Carlos Alberto Cortez Jiménez, Tumbes 2019. - Lozada Sanjinez, Ruth Ingrid Paola (2019)
ABSTRACT The purpose of this research is to identify and explain social and cultural factors; such as sex education, dysfunctional family, educational level and beliefs about sexuality are associated with teenage pregnancy. The type of research according to the purpose of the study is applied and by the contrasting design of the hypothesis; the design of the research is explanatory, the sample is represented by 28 pregnant adolescents. In order to develop the present work, a mixed approach was used, since quantitative and qualitative data were collected, analyzed and linked. Within the techniques to collect data we use: direct observation, review of sources that serve as a basis for research; within the instruments we have, the field notebook, the survey and the program that analyzes IBM SPSS data. Finally, we worked with the anthropology method, the ethnographic method, followed by the statistical method and the deductive-inductive method. Factors associated with adolescent pregnancy were: 14% have primary education as an educational level, 56.6% of adolescents began their activity before the age of 15, 71% are living with their partner, only 50% have all basic services, 46.4% have ingested a concoction as a contraceptive method, 3.6% have used contraceptive methods before becoming pregnant and 71.4% have a history of adolescent pregnancy within their family. The results show that adolescents with low education, low economic status and deficient sexual education are more likely to become pregnant during adolescence.